2003
DOI: 10.1089/107632703764664701
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Schwann Cell Adhesion in Response to Shear Stress in an in Vitro Model for Peripheral Nerve Tissue Engineering

Abstract: The design of nerve guidance channels (NGCs) is evolving to produce a favorable environment for neural regeneration. We created an in vitro model to evaluate the interactions between three centrally important components of this altered host environment: (1). Schwann cells, (2). substrate, and (3). sustained mechanical stimulus in the form of shear stress with laminar fluid flow. Preconfluent Schwann cells were plated on slides coated either with laminin, poly-D-lysine, type IV collagen, or fibronectin. These s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 55 publications
1
32
0
Order By: Relevance
“…Scramble‐transfected SCs showed 11.5% BrdU‐positive cells (Fig. 4a,c), comparable to previously reported rates (Chafik et al,2003). In contrast, β‐catenin knockdown SC cultures had significantly fewer dividing cells, showing only 5% BrdU‐positive nuclei (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Scramble‐transfected SCs showed 11.5% BrdU‐positive cells (Fig. 4a,c), comparable to previously reported rates (Chafik et al,2003). In contrast, β‐catenin knockdown SC cultures had significantly fewer dividing cells, showing only 5% BrdU‐positive nuclei (Fig.…”
Section: Resultssupporting
confidence: 91%
“…1995). Furthermore, it has been shown that when Schwann cells are subjected to shear stress in vitro , stress that mimics the mechanical stress that occurs with CNC injury, they down‐regulate mRNA and protein expression of MBP and of myelin‐associated glycoprotein (MAG) (Chafik et al. 2003; Gupta et al.…”
Section: Discussionmentioning
confidence: 99%
“…Animals with a knockout gene mutation for myelin basic protein (MBP) showed an increase in the number of SLIs per internode if both copies of the MBP gene were knocked-out (Gould et al 1995). Furthermore, it has been shown that when Schwann cells are subjected to shear stress in vitro , stress that mimics the mechanical stress that occurs with CNC injury, they down-regulate mRNA and protein expression of MBP and of myelinassociated glycoprotein (MAG) (Chafik et al 2003;Gupta et al 2005). MAG is a promyelinogenic marker in Schwann cells that is located in SLIs, as well as periaxonal cytoplasm and nodes of Ranvier (Xu et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In order to discover the most suitable linking substance, Chafik et al [89] assessed SC adhesion in vitro in response to shear stress (13.3 dyn/cm 2 ; 1 dyn=10 −5 N) in a laminar‐flow model. This is within the shear stress range known to elicit a biological response.…”
Section: Artificial Nerve Conduitsmentioning
confidence: 99%